Numerical Solutions of Free Convection Boundary Layer Flow on a Solid Sphere With Newtonian Heating in a Micropolar Fluid - Mohd Zuki, Salleh; Roslinda, Nazar; Pop, Loan (SpringerLink, 2011)
In this paper, the problem of free convection boundary layer flow on a solid sphere in a micropolar fluid with Newtonian heating, in which the heat transfer from the surface is proportional to the local surface temperature, is considered. The transformed boundary layer equations in the form of partial differential equations are solved numerically using an implicit finite difference scheme. Numerical solutions are obtained for the local wall temperature, the local skin friction coefficient, as well as the velocity, angular velocity and temperature profiles. The features of the flow and heat transfer characteristics for different values of the material or micropolar parameter, the Prandtl number and the conjugate parameter are analyzed and discussed.